Lima Beach; Landscapes of an urban seacoast - Rafael Zamora (Materia Arquitectura)
Lima is the only South American capital city on the Pacific Ocean. Since the beginning of the 20th century, its coast has had a significant development as a summer resort. Geography, architecture, society and politics have vigorously interlocked through leisure. Lima today, with nine million inhabitants, has a coastal border in a critical state, affected by neglect and pollution. In a few meters of coast of this empty shore, every summer is set a popular beach, a small and intense summer occupation that opens the way to a new leisure architecture and landscape. The article reviews four landscapes: open, in transition, reclaimed and expectant.